3 '-Sialyllactose prebiotics prevents skin inflammation via regulatory T cell differentiation in atopic dermatitis mouse models - Kang, Li-Jung; Oh, Eunjeong; Cho, Chanmi; Kwon, HoKeun; Lee, Choong-Gu; Jeon, Jimin; Lee, Hyemi; Choi, Sangil; Han, Seong Jae; Nam, Jiho; Song, Chi-une; Jung, Hyunho; et al. (NATURE PUBLISHING GROUP, 2020)
3 ' -Sialyllactose (3 ' -SL), a natural prebiotic, maintains immune homeostasis and exerts anti-inflammatory and anti-arthritic effects. Although regulatory T cells (Tregs) prevent excessive inflammation and maintain immune tolerance, the effect of 3 ' -SL on Treg regulation is unclear. This study aimed to investigate the effect of 3 ' -SL on Treg responses in atopic dermatitis (AD) pathogenesis. Oral administration of 3 ' -SL reduced AD-like symptoms such as ear, epidermal, and dermal thickness in repeated topical application of house dust mites (HDM) and 2,4-dinitrochlorobenzene (DNCB). 3 ' -SL inhibited IgE, IL-1 beta, IL-6, and TNF-alpha secretion and markedly downregulated AD-related cytokines including IL-4, IL-5, IL-6, IL-13, IL-17, IFN-gamma, TNF-alpha, and Tslp through regulation of NF-kappa B in ear tissue. Additionally, in vitro assessment of Treg differentiation revealed that 3 ' -SL directly induced TGF-beta -mediated Treg differentiation. Furthermore, 3 ' -SL administration also ameliorated sensitization and elicitation of AD pathogenesis by suppressing mast cell infiltration and production of IgE and pro-inflammatory cytokines in mouse serum by mediating the Treg response. Furthermore, Bifidobacterium population was also increased by 3 ' -SL administration as prebiotics. Our data collectively show that 3 ' -SL has therapeutic effects against AD progression by inducing Treg differentiation, downregulating AD-related cytokines, and increasing the Bifidobacterium population.
Keywords: THYMIC STROMAL LYMPHOPOIETIN; NF-KAPPA-B; MAST-CELLS; MECHANISMS; RESPONSES; IGE